BRUSHLESS DIRECT CURRENT (BLDC) MOTOR SPEED CONTROL USING FIELD ORIENTED CONTROL (FOC) METHOD - Nurdamayanti, Nurdamayanti; Sartika, Linda; Prasetia, Abdul Muis (DPTE FT UNY, 2022)
ABSTRACTBrushless DC motors or commonly known as BLDC motors are starting to be widely used in the automotive and industrial fields compared to three-phase induction motors. This is because the advantages of BLDC motors are high efficiency, large torque, and easy maintenance. Some drive systems that use BLDC motors require a constant motor speed. However, when the drive system is given more load, the speed will decrease. Therefore, we need a motor speed regulation so that the speed becomes constant even though it is given an overload. There are many ways to adjust the speed of a BLDC motor, one of which is using the Field Oriented Control method because it can adjust the field current and armature current separately. From the simulation results, the speed of the BLDC motor using the FOC method in the loaded condition, showed a better response by producing a steady state of 1494 rpm, a rise time of 0.5192 s, a settling time of 0.6362 s while not being given a load, a steady state of 1504 rpm and, a rise time of 0.533 s and a settling time of 0.64 s.ABSTRAKMotor Brushless DC atau biasa dikenal dengan motor BLDC mulai banyak digunakan pada bidang otomotif dan industri dibandingkan dengan motor induksi tiga fasa. Hal ini disebabkan karena kelebihan dari motor BLDC adalah memiliki efisiensi tinggi, torsi yang besar, dan perawatan mudah. Beberapa sistem penggerak yang menggunakan motor BLDC membutuhkan kecepatan motor yang konstan. Akan tetapi sistem penggerak tersebut ketika diberi beban lebih maka kecepatan akan menurun. Oleh karena itu dibutuhkan suatu pengaturan kecepatan motor agar kecepatan menjadi konstan walaupun diberi beban lebih. Banyak cara untuk mengatur kecepatan motor BLDC salah satunya adalah menggunakan metode Field Oriented Control karena dapat mengatur antara arus medan dan arus jangkar secara terpisah. Dari hasil simulasi didapatkan kecepatan motor BLDC menggunakan metode FOC pada kondisi berbeban, menunjukkan respon yang lebih baik dengan menghasilkan steady state yaitu 1494 rpm, rise time 0.5192 s, settling time 0.6362 s sedangkan tidak diberi beban didapatkan steady state sebesar 1504 rpm dan, rise time sebesar 0,533 s dan settling time sebesar 0,64 s.